2011
DOI: 10.1176/appi.ps.004412010
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Psychiatric Disorders Among Detained Youths

Abstract: Objective This manuscript examines the prevalence of childhood maltreatment and the relationship between childhood maltreatment and current psychiatric disorder in detained youths. Methods Clinical research interviewers assessed history of childhood maltreatment with the Child Maltreatment Assessment Profile and psychiatric diagnosis with the Diagnostic Interview Schedule for Children version 2.3 in a stratified, random sample of 1829 detained youths at the Cook Country Juvenile Temporary Detention Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 43 publications
2
73
0
Order By: Relevance
“…Our finding that prior abuse history influences the relationship between mental problems and substance use supports prior research that has investigated the relationships between abuse, substance use, and mental health 24 . Findings from the current study align with those of King et al and highlight the need for comprehensive, trauma-informed care that unifies mental health and substance use treatment.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our finding that prior abuse history influences the relationship between mental problems and substance use supports prior research that has investigated the relationships between abuse, substance use, and mental health 24 . Findings from the current study align with those of King et al and highlight the need for comprehensive, trauma-informed care that unifies mental health and substance use treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Youth with a history of child abuse are also significantly more likely to use drugs or alcohol and to be convicted for drug-related offenses 23 . In their examination of childhood maltreatment and its relationship with mental health disorders in detained youth, King et al (2011) found that both males and females who had been sexually abused (forcefully and non-forcefully) were more likely to have substance use disorder than their detained peers who were not sexually abused 24 . Specifically, among female detainees, substance abuse was prevalent among those who had been sexually abused (48%) and among those who were both sexually and physically abused (60%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent population based study in Ireland, reported rates of contact sexual abuse in 20% of girls and 16% of boys (McGhee, Garavan, Byrne, O'Higgins, & Conroy, 2011). In addition to child sexual abuse (CSA) and physical abuse (King et al, 2011;Selvi et al, 2012;Zlotnick et al, 2008), emotional abuse, physical abuse, emotional neglect and the number of types of childhood trauma suffered have also been associated with an increased likelihood of individuals subsequently suffering mental health disorders and having a reduced health-related quality of life in adulthood (Benjet, Borges, Méndez, Fleiz, & Medina-Mora, 2011;Draper et al, 2008;Huang, Schwandt, Ramchandani, George, & Heilig, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current study includes CSA, CPA, as well as neglect and exposure to DV, to examine the co-occurrence of subtypes of maltreatment and investigate the cumulative effect of different subtypes on depression. Second, studies differed in their assessment of depression, ranging from affective disorders (King et al, 2011) to general psychological functioning (Wareham & Dembo, 2007). Here, we focus on depressive symptoms.…”
mentioning
confidence: 99%